Pengaruh Tabungan Dan Deposito Terhadap Rentabilitas Bank ( Periode 2007-2014 ) - Imam Nazarudin Latif, Andi Ila Amalia, H. Eddy Soegiarto K, (EKONOMIA, 2020)
The economic growth of a country is determined by many factors, wrongone of them is banking which has the main function as an institution fundraiser from the public.The purpose of this study was to determine the Effect of Savings and Deposits against Bank Mandiri's Profitability for 2007-2014The analysis technique in this discussion uses data from Bank Mandiri's 2007-2014 financial statements and banking publication reportsIndonesia.The overall research results show that Savings has a positive effectof Bank Mandiri's profitability (ROA) 2007-2014 but not significantand Deposits have a positive effect on Bank Mandiri's Profitability (ROA) 2007-2014 but not significant.